Medical teacher can act as a best researcher - Piryani, Rano Mal (Journal of Chitwan Medical College, 2014)
DOI: http://dx.doi.org/10.3126/jcmc.v4i2.10868 Journal of Chitwan Medical College 2014; 4(2): 58